Херсонский выпуск монет Феодосия II и Валентиниана III - Коршенко, A.H. (Материалы по археологии, истории и этнографии Таврии, 2000)
В Крыму довольно часто встречаются необычные крупные позднеримские медные монеты, на аверсе которых бюст императора в оперенном шлеме, с копьем и щитом повернут вправо, а на реверсе две стоящие в полный рост фигуры держат длинный крест между собой. В легенде лицевой стороны на хороших экземплярах можно различить полностью прописанные имена Феодосия или Валентиниана. По оригинальному рисунку реверса этот тип монет может бьп'ь обозначен как “две фигуры/крест”. Локализация всех находок в Крыму, необычные стиль изображений и техника изготовления этих монет определяют необходимость рассмотреть их более подробно. About 150 specimens of large bronze coins (AE2) with helmeted bust of emperor to the right, holding a spear and shield at the obverse and two figures standing facing, wearing armour and holding each a spear and jointly a long cross at the reverse were studied. The legend has the complete name of Theodosius or Valentinian. CONCODRIA AGV (sic) and mint-mark CONS or COHS in exergue are at the reverse. These coins belong to the commemorative issue dedicated to the concordance of later Roman emperors Theodosius II and Valentinian III in 425 A.D. This event was reflected in several gold and copper types with both rulers at the reverse or with the legend CONCORDIA AVG. In contrary with others AE2 are very rare and occurred mainly (or probably only) in the vicinity of town Cherson (Crimea) which was the main Byzantine outpost in the northern part of the Black Sea. The coins mainly are very poor struck. Nevertheless 21 obverse and 32 reverse dies among specimens of both emperors were distinguished.